2004
DOI: 10.1177/107110070402501208
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Imaging of Charcot Neuroarthropathy in Diabetic Patients: Comparison of Ring PET, Hybrid PET, and Magnetic Resonance Imaging

Abstract: Introduction

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
49
0
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(54 citation statements)
references
References 12 publications
1
49
0
4
Order By: Relevance
“…Histopathologic or microbiologic confirmation of the final diagnosis was available for 10 patients. These investigators found that the mean SUVmax in uninfected neuropathic joints was 1.3 6 0.4, similar to what was reported by Hopfner et al (13). The mean SUVmax of pedal osteomyelitis in their population was 4.38 6 1.39, and the SUVmax in the one case of osteomyelitis superimposed on a neuropathic joint was 6.5.…”
supporting
confidence: 81%
See 1 more Smart Citation
“…Histopathologic or microbiologic confirmation of the final diagnosis was available for 10 patients. These investigators found that the mean SUVmax in uninfected neuropathic joints was 1.3 6 0.4, similar to what was reported by Hopfner et al (13). The mean SUVmax of pedal osteomyelitis in their population was 4.38 6 1.39, and the SUVmax in the one case of osteomyelitis superimposed on a neuropathic joint was 6.5.…”
supporting
confidence: 81%
“…The data on the role of PET and PET/CT in the evaluation of diabetic foot infections are limited (10)(11)(12)(13)(14) The mean maximum standardized uptake value (SUVmax) in these lesions was 1.8 (range, 0.5-4.1). Although image quality was superior in patients with normal blood glucose concentrations, compared with those with concentrations greater than 200 mg/dL, the sensitivity of the test was not affected by blood glucose levels.…”
mentioning
confidence: 99%
“…Ring positron emission tomography has the additional added benefit of lack of artifact in patients with metal implants such as in postsurgical CN. 31 Unfortunately, positron emission tomography is not widely available and may not be a covered service by third-party carriers for this differentiation.…”
Section: Positron Emission Tomographymentioning
confidence: 99%
“…Preoperative evaluation should focus on the bony structures involved and the presence or absence of inflammation or infection. 31 Surgery is considered prophylactic in nature with the goal of allowing the patient to safely ambulate in accommodative footwear. 24 Between 25% and 51% of patients will require surgery, including exostectomy, arthrodesis, amputation, débridement, and open reduction/internal fixation.…”
Section: Surgicalmentioning
confidence: 99%
“…было показано, что FDG-PET превосходит магнит-но-резонансную томографию (МРТ) по специ-фичности, позволяя лучше дифференциро-вать ДНОАП от остеомиелита, даже при язвах нижних конечностей [29]. Эти данные согласуются с результатами исследования Hopfner S. и соавт., которое также продемон-стрировало, что специфичность FDG-PET выше при диагностике остеомиелита у боль-ных с ДНОАП по сравнению с МРТ [30]. Совместное применение FDG-PET и КТ (FDG-PET/КТ) позволяет с высокой точностью определить локализацию поражения.…”
Section: современные возможности диагностикиunclassified